Polyphenols from Salix tetrasperma impair virulence and inhibit quorum sensing of pseudomonas aeruginosa - Mostafa, Islam; Abbas, Hisham A.; Ashour, Mohamed L.; Yasri, Abdelaziz; El-Shazly, Assem M.; Wink, Michael; Sobeh, Mansour (Molecules, 2020)
Bacterial resistance represents one of the emerging obstacles in plants, animals, and humans that impairs treatment with antibacterial agents. Targeting of the bacterial quorum sensing system is one of the strategies to overcome this problem. Recently, research has been focused on natural and food components which can function as quorum sensing inhibitors. In this study, a methanol extract from Salix tetrasperma stem bark was phytochemically profiled by LC-MS analysis. This resulted in the identification of 38 secondary metabolites with (epi)catechin-(epi)catechin, epicatechin, tremulacin, salicortin, and trichocarposide as the major constituents. The extracts of both stem bark and the previously profiled flower of S. tetrasperma were tested for anti-quorum sensing activity in a common and widely distributed pathogen Pseudomonas aeruginosa. The natural products inhibited swimming and swarming motilities, as well as proteolytic and hemolytic activities in a dose-dependent manner. Molecular docking of the constituents from both extracts against the quorum sensing controlling systems Lasl/LasR, rhll/rhlR, and PQS/MvfR showed that epicatechin, (epi)catechin-(epi)catechin, p-hydroxy benzoyl galloyl glucose, p-hydroxy benzoyl protocatechuic acid glucose, and caffeoylmalic acid could be the main active components. This study supports the importance of secondary metabolites, especially polyphenols, as quorum sensing inhibitors.
Gesehen am 04.06.2020